(untitled) (Szociológiai Szemle, 2024)
The research described in the paper has studied the family strategies of life, adjustment, the utilization of labour of those who are left without work for a long time. It gives an account of how the possibility of the utilization of labour, combined with resources of family, or perhaps of the locality, or even neighbourhood, may help those who are continuously unemployed, in survival under conditions when employment is impossible in the labour market and when they are under pressure of living conditions. However, modifications of the economy of family resources under the influence of unemployment are not free of conflict; human tensions and social losses also spring from the involuntarily narrow space of mobility. Constant reliance of large groups of permanently unemployed on social allocations and their adjustment to casual jobs, informal, black and self-sufficient work indicate the emergence of a lasting stratum depending on central redistribution and exchange relations outside the market as a paradox of marketisation.